2016
DOI: 10.24289/ijsser.283587
|View full text |Cite
|
Sign up to set email alerts
|

Pedagojik formasyon eğitimi sertifika programının matematik öğretmen adaylarının mesleki tutumlarına olan etkisi

Abstract: The purpose of this study is to identify the changes in the attitudes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Dalkılıç et al, Yıldırım and Vural, and Sever found in their studies that students who receive pedagogical formation education feel themselves more motivated towards the teaching profession because of the pedagogical education they are receiving. Altınkurt et al, Kiraz, and Dursun found out that pedagogical formation students think they will be successful in the teaching profession with the education they received and Bal found out students developed a positive attitude towards the teaching profession with this education [1,7,[53][54][55][56][57][58][59][60][61].…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Dalkılıç et al, Yıldırım and Vural, and Sever found in their studies that students who receive pedagogical formation education feel themselves more motivated towards the teaching profession because of the pedagogical education they are receiving. Altınkurt et al, Kiraz, and Dursun found out that pedagogical formation students think they will be successful in the teaching profession with the education they received and Bal found out students developed a positive attitude towards the teaching profession with this education [1,7,[53][54][55][56][57][58][59][60][61].…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…2010 yılından itibaren sayıca artan pedagojik formasyon eğitimi sertifika programları hakkındaki araştırmalarda da bu programlara olan yoğun ilginin nedenlerinin dolaylı olarak sorgulandığı görülmektedir. Bu araştırmalarda öncelikle öğretmenlik mesleği ile ilgili motivasyon (Altınkurt, Yılmaz ve Erol, 2014;Nayır ve Taneri, 2013;Polat, 2014); görüş (Aykaç, Bilgin ve Toraman, 2015;Çiçek Sağlam, 2015;Sever, Aktaş, Şahin ve Tunca, 2015), algı ve tutum (Bal, 2017;Bağçeci, Yıldırım, Kara ve Keskinpala, 2015;Demirtaş ve Aksoy, 2016;Dikmenli ve Çifçi, 2015;Eraslan ve Çakıcı, 2012;Gül ve Erkol, 2015;İlğan, Sevinç ve Arı, 2013;Kartal ve Afacan, 2012;Nartgün ve Gökçer, 2014;Özdemir ve Erol, 2015;Özkan, 2012;Üner ve Akkuş, 2016), özyeterlik algıları (Bulut ve Oral, 2011;Çocuk, Yokuş ve Tanrıseven, 2015;İpek ve Demirel, 2016;Süral ve Sarıtaş, 2015;Yazıcı ve Kalkavan, 2016), öğrenme stilleri (Güneş ve Gökçek, 2012); ve sosyal yetkinlik düzeyleri (Türkçapar, 2016) gibi konular incelenmiştir. Araştırmalar arasında pedagojik formasyon sertifika programı ile eğitim fakültesi öğrencilerinin öğretmenlik mesleğine yönelik tutum, duyarlılık, özyeterlilik inançlarının ve mesleki kimliklerinin karşılaştırıldığı çalışmalar da (Dede ve Akkoç, 2016;İncik ve Akay, 2015;Polat, 2013;Uygun, 2016) bulunmaktadır.…”
Section: Introductionunclassified